Viral infection causes a shift in the self peptide repertoire presented by human MHC class I molecules. Issue 11 (December 2015) - Spencer, Charles T.; Bezbradica, Jelena S.; Ramos, Mireya G.; Arico, Chenoa D.; Conant, Stephanie B.; Gilchuk, Pavlo; Gray, Jennifer J.; Zheng, Mu; Niu, Xinnan; Hildebrand, William; Link, Andrew J.; Joyce, Sebastian
Abstract : Purpose: MHC class I presentation of peptides allows T cells to survey the cytoplasmic protein milieu of host cells. During infection, presentation of self peptides is, in part, replaced by presentation of microbial peptides. However, little is known about the self peptides presented during infection, despite the fact that microbial infections alter host cell gene expression patterns and protein metabolism. Experimental design: The self peptide repertoire presented by HLA‐A*01;01, HLA‐A*02;01, HLA‐B*07;02, HLA‐B*35;01, and HLA‐B*45;01 (where HLA is human leukocyte antigen) was determined by tandem MS before and after vaccinia virus infection. Results: We observed a profound alteration in the self peptide repertoire with hundreds of self peptides uniquely presented after infection for which we have coined the term "self peptidome shift." The fraction of novel self peptides presented following infection varied for different HLA class I molecules. A large part (approximately 40%) of the self peptidome shift arose from peptides derived from type I interferon‐inducible genes, consistent with cellular responses to viral infection. Interestingly, approximately 12% of self peptides presented after infection showed allelic variation when searched against approximately 300 human genomes. Conclusion and clinical relevance: Self peptidome shift in a clinical transplant setting could result in alloreactivity by presenting new self peptides in the context of infection‐induced inflammation.